Therapeutic potential of archaeal unfoldase PANet and the gateless T20S proteasome in P23H rhodopsin retinitis pigmentosa mice. - Celine Brooks; Douglas Kolson; Emily Sechrest; Janelle Chuah; Jane Schupp; Neil Billington; Wen-Tao Deng; David Smith; Maxim Sokolov (PLoS ONE)
Neurodegenerative diseases are characterized by the presence of misfolded and aggregated proteins which are thought to contribute to the development of the disease. In one form of inherited blinding disease, retinitis pigmentosa, a P23H mutation in the light-sensing receptor, rhodopsin causes rhodopsin misfolding resulting in complete vision loss. We investigated whether a xenogeneic protein-unfolding ATPase (unfoldase) from thermophilic Archaea, termed PANet, could counteract the proteotoxicity of P23H rhodopsin. We found that PANet increased the number of surviving photoreceptors in P23H rhodopsin mice and recognized rhodopsin as a substate in vitro. This data supports the feasibility and efficacy of using a xenogeneic unfoldase as a therapeutic approach in mouse models of human neurodegenerative diseases. We also showed that an archaeal proteasome, called the T20S can degrade rhodopsin in vitro and demonstrated that it is feasible and safe to express gateless T20S proteasomes in vivo in mouse rod photoreceptors. Expression of archaeal proteasomes may be an effective therapeutic approach to stimulate protein degradation in retinopathies and neurodegenerative diseases with protein-misfolding etiology.